Health of community nurses: a case for workplace wellness schemes - Blake, Holly; Lee, Sandra (Mark Allen Healthcare, 2013)
Community nursing is associated with stress and burnout, which can impact heavily on the individual and the NHS both economically and on the quality of patient care. Recent Government publications have called for an increase in workplace health schemes, with the public sector ‘leading by example’. As the largest employer in Europe, the NHS is well placed to develop workplace wellness schemes to address the health needs of staff and to indirectly influence primary prevention among patients. Lessons from an innovative employee wellness programme in an NHS hospital setting demonstrates that such schemes may positively alter individual health and attitudes towards the employer. There is scope for development of such schemes to improve health and well-being in community nurses.